The Impact of Psychosocial Factors on Quality of Life among Young Women with Breast Cancer: A Systematic Review - Yuzia Melantika; Riri Maria; Yati Afiyanti; Dewi Gayatri (Indonesian Journal of Global Health Research, 2026)
Young women with breast cancer experience complex psychosocial challenges resulting from physical, emotional, and social changes during treatment, which significantly affect their quality of life (QoL). Objective to identify and analyze psychosocial aspects influencing the quality of life among young women with breast cancer. This systematic review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Literature searches were conducted across five databases (PubMed, ScienceDirect, Scopus, Sage Journals, and Taylor & Francis) for studies published between 2015 and 2025. Inclusion criteria included young women (≤40 years) diagnosed with breast cancer, using quantitative observational designs (cross-sectional or prospective cohort). A total of 11 eligible studies from 5761 articles were included and analyzed narratively. Five major themes influencing QoL were identified: (1) psychological distress (anxiety, depression, and fear of cancer recurrence); (2) sexual dysfunction and negative body image; (3) reproductive and fertility concerns; (4) social support and partner relationships; and (5) long-term QoL decline up to five years post-diagnosis, which is improved with strong social support and adaptive coping strategies. Psychosocial factors have a significant impact on the quality of life of young women with breast cancer. A holistic nursing approach that integrates psychological, social, and family support is essential to enhance emotional well-being and improve the long-term quality of life of these patients.